A research on the time-varying stiffness of the ball bearing considering the time-varying number of laden balls and load distribution. (June 2019) - Liu, Yongzhen; Zhang, Yimin
In response to the fact that not all rolling balls are laden when the angular contact ball bearing working under the condition with certain combined loads especially when the axial preload is not large enough, an analytical method for the determination of the time-varying stiffness of angular contact ball bearing considering the effect of time-varying number of laden balls and load distribution is proposed in this paper. According to the definition of the stiffness, the time-varying stiffness under different sets of combined loads is obtained by the implicit function derivation method. Only the principal diagonal elements of the stiffness matrix are studied for the sake of simplicity. Several numerical examples are simulated and the simulation results indicate that the time-varying number of laden balls and load distribution have a significant effect on the stiffness. The period of the time-varying stiffness is consistent with the time required for the cage to rotate the angle between the adjacent rolling balls. The calculation of the ball bearing quasi-static model and the analytical method for the determination of the stiffness is verified by the existing references.